2004
DOI: 10.1073/pnas.0403802101
|View full text |Cite
|
Sign up to set email alerts
|

Galmic, a nonpeptide galanin receptor agonist, affects behaviors in seizure, pain, and forced-swim tests

Abstract: The pharmacological exploitation of the galanin receptors as drug targets for treatment of epilepsy, depression, and pain has been hampered by the lack of workable compounds for medicinal chemists from random screening of large chemical libraries. The present work uses the tripeptidomimetic galnon and displays its presumed pharmacophores on a rigid molecular scaffold. The scaffold is related to marine natural products and presents three functional groups near one another in space, in a manner reminiscent of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 33 publications
0
92
0
Order By: Relevance
“…Two systemically active nonpeptide galanin receptor agonists, Galnon and Galmic, from the Langel and Rebek groups (17,29), became important pharmacological tools for studying the pharmacology of galanin signaling and represented prototypic compounds for design of improved nonpeptide ligands. Peptide analogues shorter than the endogenous galanin with receptor subtype selectivity were synthesized and characterized (36,44,45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two systemically active nonpeptide galanin receptor agonists, Galnon and Galmic, from the Langel and Rebek groups (17,29), became important pharmacological tools for studying the pharmacology of galanin signaling and represented prototypic compounds for design of improved nonpeptide ligands. Peptide analogues shorter than the endogenous galanin with receptor subtype selectivity were synthesized and characterized (36,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand competition binding of 125 I porcine galanin to the membrane preparations (29) was performed in a volume of 150 μL in a 96-well plate. Cell membranes were diluted in Hepes buffer containing 25 mM Hepes, pH 7.4, 10 mM MgCl 2 , 1 mM CaCl 2 , 0.5% BSA, and 1× protease inhibitor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in vivo experiments in rats showed that galmic penetrates the blood-brain barrier quickly and exhibits agonist-like properties that mimic the galanin neuropeptide (22). No such properties were found for cyclodiastereomer 25.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we report an example of a nonpeptide subtype selective agonist for the galanin receptor, galmic, discovered by application of a combinatorial library approach (22).…”
mentioning
confidence: 99%